A Systematic Review of the Role of Sports Diplomacy in Enhancing International Cultural Integration： Case of China International Relations - Zhang, Ziyu; Yu Wang; Kui Dong (中国科学与技术学报, 2025)
This study aimed to clarify the role of sports diplomacy in boosting international cultural integration from the perspective of international relations. The researcher used a systematic review approach—adopting repeatable analytical methods to collect and analyze data from past studies and related cases—and selected secondary sources covering both China and other countries to ensure a comprehensive understanding of sports diplomacy and its impact on cultural integration. Results showed that sports diplomacy can enhance international cultural relations via cultural interactions, management policies, and other means, but most sampled sources noted it is often used for self-serving political gains. Thus, the study concludes that the perception and application of sports diplomacy need to be adjusted to better promote cultural integration.